Student Perceptions of Learning-by-Teaching in a Speech Sound Disorders Course. - Mayne, Lesley E.; Kim, Namhee (Perspectives of the ASHA Special Interest Groups, 2022)
Purpose: The purpose of this mixed method study is to investigate graduate and undergraduate student perceptions of the benefit, content knowledge, and confidence yielded from a learning-by-teaching experience in two Communication Sciences and Disorders courses. Method: A total of 137 students, 71 graduate and 66 undergraduate students, enrolled in graduate or undergraduate sections of speech sound disorders courses participated in the study. Graduate students prepared research-based speech sound disorder intervention projects including materials that were briefly presented to undergraduate students and then interactive discussion of theory and practice with the intervention procedures and materials ensued. Pre- and poststudy quantitative and qualitative data collected from surveys of student participant perceptions were analyzed. Results: The results yielded benefits in students' satisfaction with the learning experience, content knowledge gains, and confidence as presenters at the graduate level and with implementing intervention at the undergraduate level. Conclusions: Potential implications for the learning-by-teaching as a valuable authentic pedagogical model for faculty and students in communication sciences and disorders programs are presented based on 3 years of data. This study offers faculty with a class design model to implement learning-byteaching in an existing course. Future research can investigate the benefit of embedding authentic learning experiences, such as learning-by-teaching, to formative and summative course measures and students' perceptions of preparation for practicum experiences.